USING MIXED METHODS TO EVALUATE OLDER ADULTS' EXPERIENCES WITH A CHRONIC DISEASE SELF-MANAGEMENT PROGRAM. (11th November 2018) - Greaney, M; Sands, F; Rozes, M; Morelli, A
Abstract: RI-GWEP offered a 6-week, peer-led, evidence-based chronic disease self-management program, Own Your Health (OYH), to community-dwelling older adults at 73 sites (senior centers, housing sites, religious organizations, YMCAs, and community organizations) across the state. Based on a mixed methods evaluation approach, so far 201 participants have completed assessments at baseline, post intervention (6 weeks), and follow-up (6 months). Qualitative methods (focus groups) assessed participants' experience. Most OYH participants were female (85.0%), white (76.2%). and have less than a college education (66.3%). Although OYH groups are ongoing, preliminary analyses indicate that self-efficacy for fruit/vegetable consumption (5.76 vs. 7.06, p<.001) and fruit/vegetable intake (2.50 vs. 3.45 servings, p<.001) increased from baseline to post-intervention. In contrast, there was no significant change in physical activity self-efficacy or participation. Preliminary qualitative analysis determined that participants viewed social support and feedback from OYH members as being invaluable to their change, while assessments were seen as burdensome.